Auditory Temporal Processing Tests in Unilateral and Bimodal Cochlear Implant in Pediatric Age Groups - Nagat Belkasem, (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Bilateral Cochlear Implantations (CIs) are considered the standard care for children with bilateral severe to profound sensori-neural hearing loss. However, the possibility of getting a bilateral CIs for every candidate is not always available. In order to improve speech localization, perception and language developmental, an early period of bilateral hearing aid stimulation is important for neuro-plasticity of central auditory system. So, a continuous acoustic stimulation of non-implanted ear with hearing aid (bimodal CIs) is beneficial in unilateral CIs to optimize outcome. The study was conducted to compare auditory temporal processing test in cochlear implants groups: unilateral CIs and bimodal CIs. Methods. A total of 23 cochlear implant user,14 unilateral ,9 bimodal were included in this study, their ages ranged from 6 to 13 years. Participant was assessed using pitch pattern test and duration pattern test. Results. Temporal processing ability among bimodal CIs users is significantly better than candidates with unilateral CIs. Conclusion. Our finding show that bimodal use of Cochlear implant should be recommended for those presently using unilateral device, moreover temporal processing test should be used regularly for evaluation of CI patients.